Purchasing : selection and procurement for the hospitality industry - Feinstein, Andrew Hale.; Stefanelli, John M. (Hoboken, N.J. : Wiley, 2012)
"Hospitality professionals will find that this eighth edition balances purchasing activities with product and information from a management perspective. Each chapter has been revised so that the most current concepts available are presented along with even more in-depth coverage of hospitality purchasing. Numerous examples, questions, and exercises are included to reinforce new concepts. In order to reflect changes in the field, technology applications in the purchasing function are discussed throughout. New, revised, and updated illustrations and photographs of concepts, companies, and products relating to the purchasing function have also been included to give hospitality professionals a better understanding of the field"--
The concepts of selection and procurement -- Technology applications in purchasing -- Distribution systems -- Forces affecting the distribution system -- An overview of the purchasing function -- The organization and administration of purchasing -- The buyer's relations with other company personnel -- The purchase specification: an overall view -- The optimal amount -- The optimal price -- The optimal payment policy -- The optimal supplier -- Typical ordering procedures -- Typical receiving procedures -- Typical storage management procedures-- Security in the purchasing function -- Fresh produce -- Processed produce and other grocery items -- Dairy products-- Eggs -- Poultry -- Fish -- Meat -- Beverages -- Nonfood expense items -- Services -- Furniture, fixtures, and equipment.
Includes bibliographical references and index.
Keywords: Hospitality industry -- Purchasing